IMPLEMENTASI TATA KELOLA SUMBER DAYA MANUSIA DALAM PENGATURAN OPERASIONAL BANDAR UDARA - Sunarno Sunarno (Politeknik Penerbangan Surabaya, 2019)
The aviation industry certainly cannot be separated from airports, which are the most important links between the islands of Indonesia and between other countries from all over the world. Everyone involved with airport operations must know, understand and master the important parts of an airport. This research uses qualitative research, primary data is collected through documentation and analyzed using an interactive analysis model. In connection with the needs of the aviation industry, PPI graduates in 2019 succeeded in